The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.jafc.0c04450
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Oral Bioavailability and Biotransformation of Emulsified Nobiletin Using In Vitro and In Vivo Models

Abstract: Nobiletin has received much attention for its promising biological activities. Owing to its limited solubility, various encapsulation strategies have been developed to enhance nobiletin bioavailability. However, the understanding of the bioavailability and biotransformation of nobiletin in vivo and the correlation between in vitro and in vivo data remains limited. This study developed a high-loading nobiletin (1%) emulsion. The in vitro models, which combined pH-stat lipolysis with a Franz cell, showed very go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
4
19
0
Order By: Relevance
“…However, when tangeretin was suspended in corn oil, its C max and AUClast were significantly improved but significantly lower than those of nobiletin . Similar results were reported in a recent study by Zhang et al Nobiletin also contains only one more 3′-position methoxy group than tangeretin, indicating that the group at the 3′ position improved C max and AUClast. In addition to the number of methoxy groups, human studies by Vallejo et al have shown that differences in solubility significantly alter C max and AUClast of citrus flavanones, , suggesting that water solubility is also a key factor affecting the pharmacokinetics of PMFs.…”
Section: Results and Discussionsupporting
confidence: 85%
“…However, when tangeretin was suspended in corn oil, its C max and AUClast were significantly improved but significantly lower than those of nobiletin . Similar results were reported in a recent study by Zhang et al Nobiletin also contains only one more 3′-position methoxy group than tangeretin, indicating that the group at the 3′ position improved C max and AUClast. In addition to the number of methoxy groups, human studies by Vallejo et al have shown that differences in solubility significantly alter C max and AUClast of citrus flavanones, , suggesting that water solubility is also a key factor affecting the pharmacokinetics of PMFs.…”
Section: Results and Discussionsupporting
confidence: 85%
“…In contrast, the glucuronides were present at much lower concentrations than the sulfates. Only conjugates of desmethyl nobiletin (most probably 4′-desmethyl nobiletin and 3′-desmethyl nobiletin, consistent with recent publications in rats) were detected . Several isomers were observed for some metabolites (Table ).…”
Section: Resultssupporting
confidence: 87%
“…Thus, three isomers of hydroxy-tetramethoxyflavone sulfate and two isomers of hydroxy-pentamethoxyflavone sulfate were found, as well as only one isomer of hydroxy-trimethoxyflavone sulfate and two isomers of hydroxy-pentamethoxyflavone glucuronide. The two last isomers’ occurrence is consistent with the two metabolites identified in rats after the nobiletin intake (4′-desmethyl nobiletin and 3′-desmethyl nobiletin), assuming a similar metabolism in humans …”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations